Relationship between anxiety and sexual disorders - Soewadi, Soewadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
Many factor may determine whether a marriage will be succesful or not. Among those factors, probably the important one is the desire and ability to adjust, to each other in satisfying sexual experience. In man the process of sexual activity is somewhat complicated. The act ought to be widely understood, since much human happiness depends on proper sex knowledge and adjustment. Psychological factors may play a role in the failure of sexual satisfaction.Considering the facts above, the author assumes that there will be a relationship between anxiety and sexual problem in married life. The assumption encouraged the author to study the problem.A survey of sexual problems during married life was carried out in the Special Province of Yogyakarta, among cases who proposed divorce.Results show that most of the cases with sexual problems present anxiety. A comparison between the cases with and without sexual problem, shows significant differences in the distribution of anxiety.Key Words: sexual problem - married life - anxiety - sexology - psychiatry